Microphorites (Diptera: Dolichopodidae) from the Lower Cretaceous amber of San Just (Spain), and the co-occurrence of two ceratopogonid specaies in Spanish amber deposits - Arillo, Antonio; Peñalver, Enrique; Delclòs, Xavier (Zootaxa, 2008)
A well preserved female specimen of the extinct genus Microphorites Hennig, 1971 (Diptera: Dolichopodidae) is known from San Just Amber (Lower Cretaceous, Albian, East Spain) and described as M. utrillensis nov. sp. In addition, ceratopogonids from the same deposit have been recognized as specimens of Protoculicoides skalskii Szadziewski & Arillo, 1998 and Leptoconops zherikhini Szadziewski & Arillo, 2003 two species known previously in Spanish amber from Álava. The new specimens make it possible to complete and emend the original description of P. skalskii. Palaeoecological and palaeobiogeographical comments are provided.